2017
DOI: 10.3389/fped.2017.00104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Frequency and Activation Status of Major CD4+ T-Cell Subsets after Initiation of Immunosuppressive Therapy in a Patient with New Diagnosis Childhood-Onset Systemic Lupus Erythematosus

Abstract: BackgroundSeveral studies suggest that defects of regulatory T-cells (Tregs) and impaired cellular immunity are secondary to an imbalance between auto-aggressive T-cells and Tregs in lupus patients. Discrepancies in Tregs and effector T-cells (Teff) in active lupus patients are shown to be restored in patients upon receiving immunosuppressive therapy. Therefore, our main aim was to observe frequencies of these CD4+ T-cell subsets and Tregs/Teff ratio in a new diagnosis of childhood-onset systemic lupus erythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…Our study observed a substantial increase in Treg cells in both active and inactive SLE patients compared to controls, with the most signi cant increase in active ones. This result agreed with Singla et al's(2017) [43] results, who reported a signi cant increase in Tregs in childhood SLE and mentioned that active lupus patients had a higher percentage than inactive lupus patients do. A previous study by Suarezet al (2006) [44] also observed a signi cant elevation in both active and inactive SLE patients with a maximum increase in inactive ones.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study observed a substantial increase in Treg cells in both active and inactive SLE patients compared to controls, with the most signi cant increase in active ones. This result agreed with Singla et al's(2017) [43] results, who reported a signi cant increase in Tregs in childhood SLE and mentioned that active lupus patients had a higher percentage than inactive lupus patients do. A previous study by Suarezet al (2006) [44] also observed a signi cant elevation in both active and inactive SLE patients with a maximum increase in inactive ones.…”
Section: Discussionsupporting
confidence: 92%
“…The equilibrium between the effector and regulatory T cells determines whether an autoimmune response can be triggered and propagated by autoreactive cells or not [12]. While a great deal of effort has been made to shed some light on the Treg imbalance in SLE, contradictory results have been shown [15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The failure of T cells to produce IL-2 leads to a reduction in regulatory T cells and increased effector T cells, especially the T helper 17 (Th17) phenotype. This imbalance contributes to a pro-inflammatory status in adult-onset SLE and cSLE [64][65][66]. Additionally, changes in T-cell receptors observed in SLE result in hyperactivation of their signaling pathway [64,67].…”
Section: Pathogenesismentioning
confidence: 99%
“…The only study published in jSLE was a case report of a patient with active disease where the authors demonstrated higher frequencies of PD-1 expressed in regulatory CD4 T cells, effector T cells, and naive/memory T cells. 25 After stimulation of peripheral blood cells in vitro, we observed a decrease in the production of IL-10, an antiinflammatory cytokine, and an increase in IL-23. The reduced production of IL-10 after stimulation with PHA in vitro in patients with jSLE, unlike what was observed in the control group, may suggest immune exhaustion despite the low disease activity score and the absence of clinical symptoms.…”
Section: Discussionmentioning
confidence: 85%
“…The only study published in jSLE was a case report of a patient with active disease where the authors demonstrated higher frequencies of PD-1 expressed in regulatory CD4 T cells, effector T cells, and naive/memory T cells. 25…”
Section: Discussionmentioning
confidence: 99%